2005
DOI: 10.1111/j.1365-2125.2005.02348.x
|View full text |Cite
|
Sign up to set email alerts
|

Co‐administration of ketoconazole with H1‐antagonists ebastine and loratadine in healthy subjects: pharmacokinetic and pharmacodynamic effects

Abstract: AimsTwo studies were conducted to evaluate the effects of coadministration of ketoconazole with two nonsedating antihistamines, ebastine and loratadine, on the QTc interval and on the pharmacokinetics of the antihistamines. MethodsIn both studies healthy male subjects (55 in one study and 62 in the other) were assigned to receive 5 days of antihistamine (ebastine 20 mg qd in one study, and loratadine 10 mg qd in the other) or placebo alone using a predetermined randomization schedule, followed by 8 days of con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
28
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 26 publications
5
28
0
Order By: Relevance
“…The C max value of hydroxyebastine, the major metabolite of ebastine in vitro, was approximately 50-fold lower than that of carebastine in vivo (Kang et al, 2004). A recent study by Chaikin et al (2005) has reported that ketoconazole, a potent inhibitor of CYP3A4-mediated metabolism, decreases the clearance of ebastine, leading to an accumulation of the ebastine, with little effect on the pharmacokinetics of carebastine. However, since they did not measure the change of the intermediate metabolite, hydroxyebastine, it is still open to question which P450 isoforms may contribute to the formation of carebastine.…”
mentioning
confidence: 99%
“…The C max value of hydroxyebastine, the major metabolite of ebastine in vitro, was approximately 50-fold lower than that of carebastine in vivo (Kang et al, 2004). A recent study by Chaikin et al (2005) has reported that ketoconazole, a potent inhibitor of CYP3A4-mediated metabolism, decreases the clearance of ebastine, leading to an accumulation of the ebastine, with little effect on the pharmacokinetics of carebastine. However, since they did not measure the change of the intermediate metabolite, hydroxyebastine, it is still open to question which P450 isoforms may contribute to the formation of carebastine.…”
mentioning
confidence: 99%
“…In healthy volunteers receiving ebastine 20 mg once-daily, the addition of ketoconazole 400 mg once-daily for 8 days increased AUC, C max and t max of carebastine by 1.4-, 1.1-and 3.4-fold, respectively (all P < 0.05), while these parameters increased 43-, 16-and twofold for ebastine (all P < 0.05). Carebastine t ½ increased from 25 to 81 h. Importantly, the greater exposure to ebastine and its main metabolite resulting from co-administration with ketoconazole was not accompanied by a significant increase in cardiac repolarization as measured by QTc interval (35). Co-administration of erythromycin with ebastine also altered the pharmacokinetics of ebastine and carebastine.…”
Section: Drug Interactionsmentioning
confidence: 87%
“…In addition, co-administration of either of these agents with ebastine increases the plasma concentration of ebastine (see Pharmacokinetic properties). In a study in healthy volunteers, co-administration of ebastine 20 mg/day with ketoconazole 400 mg/day for 8 days led to a statistically significant increase in QTc interval of 12 ms compared with baseline (P < 0.00001); however, this increase was not significantly different from that seen with ketoconazole alone (7 ms) (35). No participant experienced a QTc interval >500 ms.…”
Section: Cardiac Safetymentioning
confidence: 95%
See 1 more Smart Citation
“…Most often, this is achieved by including a treatment period in which subjects are dosed with a drug that mildly prolongs the QTc interval, such as a low-dose ibutilide infusion or oral moxifloxacin, a fluoroquinolone antibiotic 13,[23][24][25]. Ketoconazole, a potent hERG blocker 26), is less well characterized clinically, but has also recently been used as a positive control with an effect size that seems to meet the E14 criteria 23,27). The positive control is meant to validate the study's sensitivity, i.e.…”
Section: The E14 Documentmentioning
confidence: 99%